International Handbook of Educational Leadership and Social (In)Justice - Bogotch, Ira.; Shields, Carolyn M.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2014)
The International Handbook on Educational Leadership and Social (In)Justice creates a first-of-its-kind international forum on conceptualizing the meanings of social justice and leadership, research approaches in studying social justice and combating social injustices, school, university and teacher leadership for social justice, advocacy and advocates for social justice, socio-cultural representations of social injustices, glocal policies, and leadership development as interventions. The Handbook is as much forward-looking as it is a retrospective review of educational research literatures on social justice from a variety of educational subfields including educational leadership, higher education academic networks, special education, health education, teacher education, professional development, policy analyses, and multicultural education. The Handbook celebrates the promises of social justice while providing the educational leadership research community with concrete, contextualized illustrations on how to address inequities and combat social, political and economic injustices through the processes of education in societies and educational institutions around the world.
Part I: Conceptualizing Social Justice: More Than a Definition -- Part II: Approaches to Knowing/Studying Social Justice -- Part III: Leadership for Social Justice -- Part IV: Advocacy/Advocates for Social Justice -- Part V: Socio-Cultural Representations of Social Injustices -- Part VI: Glocal Policy Interventions -- Part VII: Leadership Preparation as Intervention -- Part VIII: Afterword.
Keywords: Education; Education -- Philosophy; Education; Administration, Organization and Leadership; Educational Policy and Politics; International and Comparative Education; Sociology of Education; Educational Philosophy